The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/antiox12020479
|View full text |Cite
|
Sign up to set email alerts
|

Blood Leukocyte ROS Production Reflects Seminal Fluid Oxidative Stress and Spermatozoa Dysfunction in Idiopathic Infertile Men

Abstract: A large proportion of infertile men do not receive a clear diagnosis, being considered as idiopathic or unexplained cases due to infertility diagnosis based on standard semen parameters. Particularly in unexplained cases, the search for new indicators seems mandatory to provide specific information. In the etiopathogenesis of male infertility oxidative stress displays important roles by negatively affecting sperm quality and function. In this study, performed in a population of 34 idiopathic infertile men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It is clearly established that ROS can promote coagulation through several means, such as enhancing the expression of tissue factor in endothelial cells, monocytes, and vascular smooth muscle cells, interfering with platelet activation, and causing oxidative structural and functional alterations to crucial proteins involved in the coagulation cascade (e.g., tissue factor pathway inhibitor (TFPI), protein C, thrombomodulin, fibrinogen, antithrombin) ( Gray and Barrowcliffe, 1985 ; Glaser et al, 1992 ; Freedman et al, 1999 ; Van Patten et al, 1999 ; Ohkura et al, 2004 ; Nalian and Iakhiaev, 2008 ; Pensalfini et al, 2008 ; Barr et al, 2013 ; Barygina et al, 2013 ; Becatti et al, 2013 ; Becatti et al, 2015 ; Dayal et al, 2015 ; Becatti et al, 2016b ; Becatti et al, 2017 ; Barygina et al, 2019a ; Barygina et al, 2019b ; Becatti et al, 2019b ; Emmi et al, 2019b ; Becatti et al, 2020 ; Branca et al, 2020 ; Cito et al, 2020 ; Ianni et al, 2021 ; Mannucci et al, 2021 ; Bettiol et al, 2022 ; Becatti et al, 2023 ). Additionally, ROS can facilitate thrombo-inflammation, including via hyperactivation of leukocytes, particularly neutrophils, and the release of neutrophil extracellular traps (NETs) ( Bettiol et al, 2021 ).…”
Section: Sirt1 and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly established that ROS can promote coagulation through several means, such as enhancing the expression of tissue factor in endothelial cells, monocytes, and vascular smooth muscle cells, interfering with platelet activation, and causing oxidative structural and functional alterations to crucial proteins involved in the coagulation cascade (e.g., tissue factor pathway inhibitor (TFPI), protein C, thrombomodulin, fibrinogen, antithrombin) ( Gray and Barrowcliffe, 1985 ; Glaser et al, 1992 ; Freedman et al, 1999 ; Van Patten et al, 1999 ; Ohkura et al, 2004 ; Nalian and Iakhiaev, 2008 ; Pensalfini et al, 2008 ; Barr et al, 2013 ; Barygina et al, 2013 ; Becatti et al, 2013 ; Becatti et al, 2015 ; Dayal et al, 2015 ; Becatti et al, 2016b ; Becatti et al, 2017 ; Barygina et al, 2019a ; Barygina et al, 2019b ; Becatti et al, 2019b ; Emmi et al, 2019b ; Becatti et al, 2020 ; Branca et al, 2020 ; Cito et al, 2020 ; Ianni et al, 2021 ; Mannucci et al, 2021 ; Bettiol et al, 2022 ; Becatti et al, 2023 ). Additionally, ROS can facilitate thrombo-inflammation, including via hyperactivation of leukocytes, particularly neutrophils, and the release of neutrophil extracellular traps (NETs) ( Bettiol et al, 2021 ).…”
Section: Sirt1 and Oxidative Stressmentioning
confidence: 99%
“…Also, leukocyte-derived ROS can induce the oxidation of fibrinogen, resulting in an altered secondary structure and overall clot architecture, displaying reduced porosity and a tight fibrin network with filaments of reduced average size ( Miniati et al, 2010 ; Becatti et al, 2014b ; Becatti et al, 2016c ; Becatti et al, 2020 ). These oxidative alterations lead to dysfunctional fibrinogen features, both in terms of thrombin-catalyzed fibrin polymerization and susceptibility to plasmin-induced lysis ( Pensalfini et al, 2008 ; Miniati et al, 2010 ; Barygina et al, 2013 ; Becatti et al, 2013 ; Cellai et al, 2013 ; Becatti et al, 2014b ; Cellai et al, 2014 ; Lami et al, 2014 ; Becatti et al, 2015 ; Becatti et al, 2016b ; Becatti et al, 2016c ; Becatti et al, 2017 ; Barygina et al, 2019a ; Barygina et al, 2019b ; Becatti et al, 2019b ; Emmi et al, 2019b ; Becatti et al, 2020 ; Branca et al, 2020 ; Cito et al, 2020 ; Ianni et al, 2021 ; Mannucci et al, 2021 ; Bettiol et al, 2022 ; Becatti et al, 2023 ).…”
Section: Sirt1 and Oxidative Stressmentioning
confidence: 99%
“…OAT may be directly linked to oxidative stress (OS) [8]. Previous clinical trials [9][10][11] have shown significant reactive oxygen species amounts in the semen of individuals with OAT, and animal experiments [12,13] have shown significantly increased 8-hydroxy-deoxyguanosine (8-OHdG) and malondialdehyde (MDA) levels in the testis of OAT rats. This indicates that OSmediated testicular injury may be the core mechanism underlying the occurrence of OAT.…”
Section: Introductionmentioning
confidence: 99%